Serologically assessed markers of fibroblast activity (PRO-C3 and PRO-C6) and risk assessment of pulmonary fibrosis following severe COVID-19 infection - Anne Orholm Nielsen; Kirsten Brændholt Rasmussen; Frederikke Bay Toft; Henning Bay Nielsen; Thomas Hildebrandt; Carsten Sloth; Alejandro E. Mayorca-Guiliani; Morten Karsdal; Diana Julie Leeming; Rikke Borg (European Clinical Respiratory Journal)
Background Impaired lung function and fibrotic scarring of the lungs following severe COVID-19 infection are well-known manifestations. However, the risk factors and predisposing factors are still unknown. This study explored whether serological biomarkers for collagen synthesis associate with impaired lung function and fibrotic scarring after COVID-19 infection.Methods In a prospective, observational cohort study involving patients hospitalized with COVID-19 requiring intensive care from June 2020 to December 2021, patients were followed up at 1, 3, 6, and 12 months after discharge. Lung function, diffusion capacity, and a panel of serological biomarkers for collagen-based fibrogenesis (PRO-C3, PRO-C6, and PRO-FIB) were measured. Additionally, a high-resolution CT scan of the lungs was performed at 3 and 12 months.Results Thirty-four patients were included in the study. Twenty-seven (80%) were men (mean age 61 years). Most patients were former or active smokers (56%), while 44% were never smokers. Levels of both PRO-C3, PRO-C6, and PRO-FIB were higher 3 months after discharge compared to the normal range. The highest levels were measured 1 month after discharge, with PRO-C3 23.2 ng/ml, PRO-C6 15.9 ng/ml, and PRO-FIB 29.3 ng/ml. The levels of PRO-C3 declined up to 6 months after discharge and were hereafter stabilized, whereas the levels of PRO-C6 declined for the entire follow up period. Lung function improved during the first 6 months and then stabilized. Comparing lung function with PRO-C3 and PRO-C6 showed a positive correlation with lung function improving, while levels of the biomarkers declined. However, only PRO-C3 was found to be significantly associated with improvement in lung function 1 month after discharge.Conclusions This study found that PRO-C3 and PRO-C6 are associated with changes in lung function after severe COVID-19 infection. High levels of both PRO-C6 and PRO-C3 were found up to 6 months after discharge in patients with impaired lung function, however, the values declined towards reference levels after 12 months.